The Role of Educational Practice in the Learning of Basic Psychological Concepts (Based on Practical Training of 1st year Master Students Studying "Cultural-Historical Psychology and Activity Approach in Education") - Ulanovskaya I. M. (Moscow State University of Psychology and Education, 2015)
The article describes experience of the practical training for 1st year master students studying «cultural-historical psychology and activity approach in education» entitled "Study of the educational environment of the school". The basis for training was provided by Moscow school #91 which systematically implemented in the elementary school the program of developing training, developed in the framework of Elkonin-Davydov theory of learning activity. There are examples of tools proposed and developed by teams of master students to evaluate certain characteristics of the educational environment and the results of their use to solve diagnostic problems. It is shown how techniques of deep studying, setting difficult practically significant substantive issues, independent work, group discussions, group projects development and defence, the master students applied, contribute to the formation of the bases of professional critical thinking, reflection and cognitive attitudes.